2012
DOI: 10.3892/ol.2012.613
|View full text |Cite
|
Sign up to set email alerts
|

HGF stimulates proliferation through the HGF/c-Met pathway in nasopharyngeal carcinoma cells

Abstract: Abstract. Hepatocyte growth factor (HGF) and its receptor c-Met are important in the development and homeostasis of a variety of human malignancies. However, the role of the HGF/c-Met signaling pathway in nasopharyngeal carcinoma (NPC) has not been clearly elucidated. This study examined the effect of HGF/c-Met on proliferation and migration in several NPC cell lines. RT-PCR was used to detect the HGF gene in CNE-1, CNE-2, HK-1, HONE-1 and SUNE-1 NPC cells. However, HGF gene expression was not detected in any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Cells harboring different dominant signaling pathways could react differently to HGF. The 97L cell line employed in our study has been reported to express the c-Met receptor [29], which suggests that the HGF/c-Met pathway is most likely the main mechanism through which H-CAFs induce HCC cell proliferation at least in 97L cells. In summary, HGF appears to play a substantial role in the complex mechanisms involved in the proliferative induction of HCC by H-CAFs.…”
Section: Discussionmentioning
confidence: 85%
“…Cells harboring different dominant signaling pathways could react differently to HGF. The 97L cell line employed in our study has been reported to express the c-Met receptor [29], which suggests that the HGF/c-Met pathway is most likely the main mechanism through which H-CAFs induce HCC cell proliferation at least in 97L cells. In summary, HGF appears to play a substantial role in the complex mechanisms involved in the proliferative induction of HCC by H-CAFs.…”
Section: Discussionmentioning
confidence: 85%
“…FGF members have showed to promote not only fibroblast proliferation but also migration and differentiation through binding to and activating fibroblast growth factor receptors, thereby having its application in tissue regeneration (Yun et al, 2010 ). Besides, HGF and PDGF-BB are important multifunctional growth factors for cell proliferation and mobility (Taniguchi et al, 2004 ; De Donatis et al, 2008 ; Sun et al, 2012 ; Gonzalez et al, 2017 ; Dai et al, 2018 ). However, TGF-β that is reported to regulate fibroblast proliferation through miR-21 modulating PTEN/AKT signaling pathway (Liu et al, 2016 ) or to induce ERK/MAPK signaling pathway to enhance migration of endometrial stromal cells (Liu et al, 2019 ) was not detected in BMMSC- and ADMSC-derived exosomes in this study.…”
Section: Discussionmentioning
confidence: 99%
“…HGF has been shown to promote cell migration and invasion [42], [65], [66] and is required in cell migration assays. The EGFR inhibitors were ineffective in blocking cell migration in all of the cell lines (A549, H1975 and H1650) except for EGFR wildtype cell line H292 which was sensitive to EGFR inhibitors.…”
Section: Discussionmentioning
confidence: 99%